Anaesthesia and ICU sedation with sevoflurane do not reduce myocardial injury in patients undergoing cardiac surgery: A randomized prospective study. Issue 50 (11th December 2020) - Guinot, Pierre-Grégoire; Ellouze, Omar; Grosjean, Sandrine; Berthoud, Vivien; Constandache, Tiberiu; Radhouani, Mohamed; Anciaux, Jean-Baptiste; Aho-Glele, Serge; Morgant, Marie-Catherine; Girard, Claude; Nguyen, Maxime; Bouhemad, Belaid
Abstract: Background: To evaluate the effect of anaesthesia and ICU sedation with sevoflurane to protect the myocardium against ischemia-reperfusion injury associated to cardiac surgery assessed by troponin release. Methods: We performed a prospective, open-label, randomized study in cardiac surgery with cardiopulmonary bypass. Patients were randomized to an algorithm-based intervention group and a control group. The main outcome was the perioperative kinetic of cardiac troponin I (cTnI). The secondary outcomes included composite endpoint, GDF-15 (macrophage inhibitory cytokine-1) value, arterial lactate levels, and the length of stay (LOS) in the ICU. Results: Of 82 included patients, 81 were analyzed on an intention-to-treat basis (intervention group: n = 42; control group: n = 39). On inclusion, the intervention and control groups did not differ significantly in terms of demographic and surgical data. The postoperative kinetics of cTnI did not differ significantly between groups: the mean difference was 0.44 ± 1.09 μg/ml, P = .69. Incidence of composite endpoint and GDF-15 values were higher in the sevoflurane group than in propofol group. The intervention and control groups did not differ significantly in terms of ICU stay and hospital stay. Conclusion: The use of an anaesthesia and ICU sedation with sevoflurane was not associated with a lower incidence of myocardial injury assessed by cTnI. Sevoflurane administration was associated with higher prevalence of acute renal failure and higher GDF-15 values.